Hubungan Usia dan Paritas Ibu Hamil dengan Kejadian Perdarahan Antepartum di RSIA Artha Mahinrus Medan Tahun 2022 - Damayanti S, Damayanti S; Armita S, Marta (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2023)
Until now, antepartum hemorrhage still plays an important role as the main cause of death, even in developed countries. In 2021 there were 87 cases of antepartum bleeding at RSIA Artha Mahinrus Medan. The purpose of this research is to determine the relationship between age and parity of pregnant women with the incidence of antepartum bleeding at RSIA Artha Mahinrus Medan. This type of research is quantitative with a "cross sectional" approach. The study population was pregnant women who had their pregnancies checked at Mother And Child Hospital Artha Mahinrus Medan, totaling 1,033 respondents, while the study sample totaling 289 was determined from the solvin formula, which was obtained by systematic random sampling, measuring instrument observation sheet. The analysis used univariate to determine the percentage and bivariate to determine the relationship between the dependent and independent variables. The resultsshowed that the frequency distribution of respondents was based on parity 1 and >3 years (42.2%), respondents aged <20 and >35 years (47.1%), respondents who experienced antepartum bleeding (30.1%), there were relationship between parity (p value 0.000), and age with antepartum bleeding (p value 0.000). To health workers to further improve public health education in hospitals by providing leaflets, counseling and counseling to pregnant women.